Design, Automation and Test in Europe
DOI: 10.1109/date.2005.278
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Modeling of Pipeline Delay and Design of Pipeline under Process Variation to Enhance Yield in sub-100nm Technologies

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 9 publications
0
12
0
Order By: Relevance
“…For instance, a recent study on the effects of process variations on microprocessors has shown that the L1 cache has almost 60% chances of containing the critical path [10]. Another study also reports that process variations can have an uneven impact on the timing of different pipeline stages of a sequential circuit [1].…”
Section: Impact Of Process Variations On Timingmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, a recent study on the effects of process variations on microprocessors has shown that the L1 cache has almost 60% chances of containing the critical path [10]. Another study also reports that process variations can have an uneven impact on the timing of different pipeline stages of a sequential circuit [1].…”
Section: Impact Of Process Variations On Timingmentioning
confidence: 99%
“…Majority of existing statistical yield optimization techniques are static [1][2][3][4]. However, we propose a dynamic technique that enables robustness towards process variations during run-time.…”
Section: Introductionmentioning
confidence: 99%
“…Tschanz et al [7] propose adaptive body bias (ABB) and Narendra et al [11] propose forward body bias (FBB) to mitigate the impact of variation for several critical path structures, but neither of these studies consider system-level effects. Datta et al demonstrate that an unbalanced pipeline design can increase yield [5].…”
Section: Related Workmentioning
confidence: 99%
“…In the NT regime, the pipelined circuits should be designed not only energy-efficient, but also variability-tolerant. The authors in [11] developed a statistical methodology to enhance the yield of the pipelined circuits, considering the inter-die and intra-die variation. Recently, a two-phase latch-based design strategy is proposed for the synchronous pipelined circuits in the NT operation regime to derive the optimal ratio between the total width of sequential logic and that of combinational logic [10].…”
Section: Introductionmentioning
confidence: 99%